Foetal and Perinatal Autopsy – A Study Of 100 Cases - Choukimath, Sharanabasav M; Giriyan, Sujata S; Bargunam, Priyadharshini (Annals of Pathology and Laboratory Medicine, 2019)
Background: Perinatal and foetal Autopsy pave way for bringing down these preventable stillbirths by identifying the potential areas where the health system tend to fail and helps to rule out congenital and infectious diseases and hence their recurrence. Aims: To describe and analyse the foetal and perinatal death. To determine how often the perinatal autopsy determines and confirms the cause of death and how often it changes the clinical diagnosis. Methods and Material: Autopsy was performed by the pathologist after obtaining informed written consent from parents, examining grossly and microscopically. The cause of death, whenever found was classified according to the ReCoDe system of classification of cause of death. Results: Cause of death was found in 101 (96.2%), unknown in 4 cases (3.8%). Foetal causes were found in 55 (52.4%), lethal Congenital Malformation was seen in 31 (29.5%) cases. Maternal causes were seen in 21 (20%), placental causes were seen in 11 (10.5%) cases. Other causes were attributed in 14 (13.3%) cases. Autopsy added significant findings to the prenatal diagnosis in 10 cases (10%) and changed and added new findings in (9%) 9 cases. While in (81%) 81 cases, it had confirmed the clinical diagnosis. Conclusions: Despite technological advancements, foetal autopsy remains gold standard for diagnosing the cause of death of foetus thus helping prenatal counselling.